Anti‐CD20 inhibits T cell‐mediated pathology and microgliosis in the rat brain. (16th September 2014) - Anthony, Daniel C.; Dickens, Alex M.; Seneca, Nicholas; Couch, Yvonne; Campbell, Sandra; Checa, Begona; Kersemans, Veerle; Warren, Edward A.; Tredwell, Matthew; Sibson, Nicola R.; Gouverneur, Veronique; Leppert, David
Abstract Objective The mechanism of action of anti‐B cell therapy in multiple sclerosis (MS) is not fully understood. Here, we compared the effect of anti‐CD20 therapy on microglial activation in two distinct focal rat models of MS. Methods The effect of anti‐CD20 therapy on lesion formation and extralesional microglial activation was evaluated in the fDTH‐EAE (experimental allergic encephalomyelitis) model, which is a focal demyelinating type‐IV delayed‐type hypersensitivity lesion. For comparison, effects were also assessed in the focal humoral MOG model induced by intracerebral injection of cytokine in myelin oligodendrocyte glycoprotein immunized rats. Microglial activation was assessed in situ and in vivo using the TSPO SPECT ligand [125I]DPA‐713, and by immunostaining for MHCII. The effect of treatment on demyelination and lymphocyte recruitment to the brain were evaluated. Results Anti‐CD20 therapy reduced microglial activation, and lesion formation in the humoral model, but it was most effective in the antibody‐independent fDTH‐EAE. Immunohistochemistry for MHCII also demonstrated a reduced volume of microglial activation in the brains of anti‐CD20‐treated fDTH‐EAE animals, which was accompanied by a reduction in T‐cell recruitment and demyelination. The effect anti‐CD20 therapy in the latter model was similarly strong as compared to the T‐cell targeting MS compound FTY720. Interpretation The suppression of lesion development by anti‐CD20 treatment in an antibody‐independent model suggests that B‐cells play an important role in lesion development, independent of auto‐antibody production. Thus, CD20‐positive B‐cell depletion has the potential to be effective in a wider population of individuals with MS than might have been predicted from our knowledge of the underlying histopathology.